Geografia intelligente e user experience: lotta a due tra Google e Apple nel mondo delle informazioni geospaziali per tutti - Domenico, Santarsiero (GEOmedia, 2016)
The world of intelligent geography, namely the different applications in the past decade have brought digital geography and the world of geospatial information to the consumer market, is represented by three of the competitors in the computer industry and the new era dell`ICT: Google, Microsoft and Apple. The latter has released the MAPS system within the last four years (2012), first only on the iOS platform (iPhone and iPad) and later on its desktop OS, Mavericks. It is from then that MAPS, provided by default, represents the real revolution in the field of 3D Geospatial for the consumer market, a potentially infinite market, composed of billions of people who use smartphone, tablet or PC. The war of the maps still continues, even though the world of geomatics seems not to notice.